12-Step Programs to Reduce Illicit Drug Use - Nielsen, Sine Kirkegaard; Filges, Trine; Jørgensen, Anne-Marie Klint (International Journal of Criminology and Sociology, 2014)
Many treatments are not rigorously evaluated as to their effectiveness, and it is uncertain which types of interventions are more effective than others in reducing illicit drug use. The aim of this paper is to provide a systematic mapping of the research literature of the effectiveness of 12-step programs in reducing illicit drug use. A systematic literature search was conducted based on 17 international and Nordic bibliographic databases. A total of 15,993 references were screened, and eleven unique studies were finally included in this mapping. The included studies demonstrated conflicting results regarding the effectiveness of the 12-step treatment and TSF in reducing individuals’ drug use. Two studies reported a positive effect of the TSF treatment compared to the comparison conditions in reducing drug use. Six studies reported no differences between the 12-step program and the comparison condition, and the remaining three studies reported a greater effect of the comparison condition. However, the included studies demonstrate that, in general, 12-step programs and the comparison conditions have some positive effects in reducing drug use and supporting abstinence among the participants.